A computer-assisted analysis of Zhu Fonian's original Mahāyāna sutras - Lin, Qian; Radich, Michael (Buddhist studies review, 2021)
In her 2010 study of the Shi zhu duan jie jing T309, Jan Nattier found that several passages in T309 were copied from earlier Chinese Buddhist texts. She thus proposed that T309 is not a translation from an Indian text, but a “forgery” by Zhu Fonian. Extending Nattier’s analysis with the help of TACL, a tool for computational textual analysis, we conducted a more thorough analysis of Zhu Fonian’s four Mahayana texts, namely, T309, the Pusa chu tai jing T384, the Zhongyin jin T385, and the Pusa yingluo jing T656, and found in T309 and T656 additional content deriving from earlier Chinese texts. On the basis of this analysis of these features of the texts, we propose that all four were likely compiled by Zhu Fonian himself.
Gesehen am 03.12.2025